تقدير مؤشرات الوثوقية للآلات القابلة للإصلاح دراسة تطبيقية في شركة الساحل للغزل - منصور, يمن (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The aim of the research is to identify the basic indicators of the reliability of the machines that can be repaired. The aim of these indicators is to estimate some of the machines of the Alsahel spinning company in the city of Jableh, using the negative exponential probability distribution and the Weibull distribution, whichever is the best, as they are one of the most important probability distributions used in the study of reliability. The main results of the research were as follows: - The failure of most of the studied machines is classified as a failure of usage and consumption, as it has been in use for more than fifteen years. - It was found the rates of failure and repair of most machines studied increased with increasing time. - Both the reliability and repair functions of all machines studied have decreased significantly for increasing periods of time. - All the studied machines were well prepared, and the probability of being in the repair was small, due to Subject to preventive maintenance, and the initiative to repair any malfunction immediately. - The reliability of most studied machines was generally low during the study period. هدف البحث إلى التعرف على المؤشرات الأساسية لوثوقية الآلات القابلة للإصلاح ، كما هدف إلى تقدير هذه المؤشرات لبعض آلات شركة الساحل للغزل في مدينة جبلة ، وذلك باستخدام التوزيعين الاحتماليين الأسي السالب ووايبول أيهما الأفضل، كونهما من أهم التوزيعات الاحتمالية التي تستخدم في دراسة الوثوقية. وتمثلت أهم نتائج البحث بالآتي: - تصنف أعطال معظم الآلات المدروسة ضمن أعطال الاستخدام والاستهلاك، حيث أنها وضعت في الاستخدام منذ فترة تتجاوز خمسة عشر عاماً. - تبين أن معدلات التعطل والإصلاح لمعظم الآلات المدروسة متزايدة مع تزايد الزمن. - تناقص كل من دالتي الوثوقية والإصلاح لجميع الآلات المدروسة بشكل واضح من أجل فترات زمنية متزايدة. - كانت جاهزية جميع الآلات المدروسة جيدة ، كما كان احتمال كونها في الإصلاح صغيراً ، وذلك بسبب خضوعها لعمليات الصيانة الوقائية ، وبسبب المبادرة لإصلاح أي عطل فور حدوثه. - وثوقية معظم الآلات المدروسة كانت منخفضة بشكل عام خلال فترة الدراسة.